Pelatihan Manajemen Agrowisata di Desa Sungai Langka Kabupaten Pesawaran, Lampung - Wan Abbas Zakaria; Lidya Sari Mas Indah (Universitas Mathla'ul Anwar Banten, 2021)
AGRO-TOURISM MANAGEMENT TRAINING IN SUNGAI LANGKA VILLAGE, PESAWARAN DISTRICT, LAMPUNG. Sungailangka Village is a village in Pesawaran District which has been named an agro-tourism village by the Lampung Provincial Government. This PKM Aims (1) increase the knowledge and skills of village government officials and the community regarding agro-tourism management, (2) inventory the potential of Sungailangka Agro-tourism Village. The method used is Focus Group Discussion (FGD). The results of the post-test from this PKM showed that the level of participants' knowledge about agro-tourism managemnt had increased by about 70 percent. The potential for agro-tourism in Sungai Langka Village includes the potential for agriculture, plantations, the environment, and home industry. The leading businesses in Sungailangka Village include a variety, including: (1) citrus picking tours and salak garden tours, (2) various kinds of chips (jackfruit, banana, and zalacca), (3) handicrafts (4) culinary: (bumbu pecel, cocoa powder), and (5) and goat farm (etawa goat's milk).